THE ROLE OF DIGITAL TOOLS AND ITS IMPACT IN TEACHER EDUCATION - Toshboltaev Fakhriddin Urinboevich,; Vakhobjonova Muniraxon Hasanboy Qizi, (Ustozlar uchun, 2025)
This article explores the integration of digital tools in teacher education and examines their impact on teaching practices, classroom management, and student engagement. The text emphasizes the growing necessity for educators to embrace technology to improve the teaching and learning experience. It outlines several key digital tools, such as Learning Management Systems (LMS), virtual simulations, collaborative platforms, content creation software, assessment tools, and gamification platforms. These tools enhance teachers' ability to design engaging, interactive lessons, foster collaboration, and personalize learning. The article also discusses the positive outcomes of digital tool integration, including improved pedagogical competence, personalized learning, better classroom management, and enhanced collaboration among teachers. However, the text acknowledges challenges such as unequal access to technology, resistance to change, the need for ongoing professional development, and concerns about over-reliance on technology. Overall, it highlights the transformative potential of digital tools in teacher education, arguing that with proper support and resources, technology can help prepare future educators for the demands of modern classrooms.